Caffeine and brain computer interfaces: discerning impact on fatigue and concentration - Kwah, Hwee Kiat (Nanyang Technological University, 2022)
Brain-Computer Interface (BCI) is a relatively novel way to communicate with and through computers. The interaction with BCI by humans ideally requires clear signals to ensure unambiguous interpretation by the computer. However, any surgical intrusion into the brain will pose health risks for an average person. Existing research have shown that Electroencephalograms (EEG) which are obtained from the scalp level could identify the state of mind and even provide motor imagery. In real time applications such as the above, it is imperative to take into consideration obstacles faced by EEG. One of the obstacles is fatigue. Existing studies have shown that fatigue could be detected by EEG. However, there are limits to the capability of prolonged EEG usage. One of the ways to prolong mental alertness is through stimulants. Caffeine is one of the common stimulants consumed by a person. This study aims to analyse the impact of caffeine on EEG through analysing of spectrum parameters. The delta band spectrum in this study have shown changes with regards to fatigue and coffee consumption. The experimental results are provided in the report